2008
DOI: 10.1073/pnas.0806896105
|View full text |Cite
|
Sign up to set email alerts
|

A type II NAD(P)H dehydrogenase mediates light-independent plastoquinone reduction in the chloroplast of Chlamydomonas

Abstract: In photosynthetic eukaryotes, nonphotochemical plastoquinone (PQ) reduction is important for the regulation of photosynthetic electron flow. In green microalgae where this process has been demonstrated, the chloroplastic enzyme that catalyses nonphotochemical PQ reduction has not been identified yet. Here, we show by an RNA interference (RNAi) approach that the NDA2 gene, belonging to a type II NAD(P)H dehydrogenases family in the green microalga Chlamydomonas reinhardtii, encodes a chloroplastic dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
157
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 45 publications
4
157
0
Order By: Relevance
“…The ETR did not exceed 5 e -s -1 PSI -1 in pgrl1 hydg-2 double mutant and might correspond to an NDA2-driven ETR (Jans et al, 2008;Alric, 2014). The low rate measured here is in good agreement with the rate of 2 e -s -1 PSI -1 measured for PQ reduction by NDA2 (Houille-Vernes et al, 2011) and the rate of 50 to 100 nmol H 2 mg chlorophyll -1 min -1 determined for NDA2-driven H 2 production from starch degradation (Baltz et al, 2014), the latter value also corresponding to approximately 1 to 2 e -s -1 PSI -1 , assuming 500 chlorophyll per photosynthetic unit (Kolber and Falkowski, 1993).…”
Section: Sequential and Transient Hydrogenase Activity And Psi-cef Comentioning
confidence: 85%
See 1 more Smart Citation
“…The ETR did not exceed 5 e -s -1 PSI -1 in pgrl1 hydg-2 double mutant and might correspond to an NDA2-driven ETR (Jans et al, 2008;Alric, 2014). The low rate measured here is in good agreement with the rate of 2 e -s -1 PSI -1 measured for PQ reduction by NDA2 (Houille-Vernes et al, 2011) and the rate of 50 to 100 nmol H 2 mg chlorophyll -1 min -1 determined for NDA2-driven H 2 production from starch degradation (Baltz et al, 2014), the latter value also corresponding to approximately 1 to 2 e -s -1 PSI -1 , assuming 500 chlorophyll per photosynthetic unit (Kolber and Falkowski, 1993).…”
Section: Sequential and Transient Hydrogenase Activity And Psi-cef Comentioning
confidence: 85%
“…By generating an additional transthylakoidal proton gradient without producing reducing power, this AEF thus contributes to adjust the ATP/NADPH ratio for carbon fixation in various energetic unfavorable conditions including anoxia (Tolleter et al, 2011;Alric, 2014), high light (Tolleter et al, 2011;Johnson et al, 2014), or low CO 2 (Lucker and Kramer, 2013). In C. reinhardtii, two pathways have been suggested to be involved in PSI-CEF: (1) a type II NAD(P)H dehydrogenase (NDA2; Jans et al, 2008) driving the electrons from NAD(P)H to the PQ pool and (2) a pathway involving Proton Gradient Regulation (PGR) proteins where electrons from reduced FDXs return to the PQ pool or cytochrome b 6 f. Not fully understood, this latter pathway comprises at least Proton Gradient Regulation5 (PGR5) and ProtonGradient Regulation-Like1 (PGRL1) proteins (Iwai et al, 2010;Tolleter et al, 2011;Johnson et al, 2014) and is the major route for PSI-CEF in C. reinhardtii cells placed in anoxia (Alric, 2014).…”
mentioning
confidence: 99%
“…In mixotrophic conditions, when compared to wild type, complex I mutants of Chlamydomonas are slightly more towards state II transition of the photosynthetic apparatus (Cardol et al, 2003), a condition in which plastoquinones are reduced by the activity of the NAD(P)H dehydrogenase Nda2 (Jans et al, 2008), LHCII are phosphorylated and associated to PSI (reviewed in Lemeille and Rochaix, 2010). In complex I-deficient cells, we found that two protein spots corresponding to LHCII proteins Lhcb5/CP26 and Lhcbm2 were less abundant than in wild type but this was not paralleled with a change in other LHCII protein amounts, PSII-LHCII amount, or PSII absorption cross section.…”
Section: Discussionmentioning
confidence: 99%
“…may have two direct and two indirect pathways for CEF (Jeanjean et al, 1999), whereas there are only two known pathways in vascular plants and green algae (Chlamydomonas reinhardtii): proton gradient regulation5 (PGR5) dependent and NADPH dehydrogenase (NDH) dependent. Vascular plants have a multisubunit type I NDH that is active in chloroplast thylakoids and also reduces plastoquinone in an Fd-dependent manner (Burrows et al, 1998;Kofer et al, 1998;Shikanai et al, 1998;Yamamoto et al, 2011), whereas in green algae, the type II NADPH dehydrogenase2, NDA2, has been implicated in electron recycling through NADPH (Jans et al, 2008). Arabidopsis (Arabidopsis thaliana) mutants devoid of both PGR5 and Chlororespiratory reduction pathways (pgr5 crr-1) can only sustain very poor photosynthetic growth (Munekage et al, 2004), illustrating the requirement of these pathways for efficient photosynthesis.…”
mentioning
confidence: 99%